Conversão termoquímica de capim-elefante em reator rotativo - De Conto, Daniela (My University, 2016)
In recent years, renewable energy has received increased importance due to increased anthropogenic emissions of greenhouse gases to the atmosphere. Biomass is a promising renewable resource for the production of energy. Pyrolysis is one of the most promising thermal conversion technologies, creating value-added products, especially from other sources of renewable energy. In the present study addressed the thermal conversion (pyrolysis) of elephant grass (Pennisetum purpureum S.) in a rotating reactor in order to determine the best operating conditions (temperature and speed) for the production of hydrogen. The elephant grass was subjected to various characterization tests by elemental analysis (CHNS) and immediate, analysis chemical (lignin, cellulose, hemicellulose and extractives) higher heating value, particle size analysis, metal analysis and non-metals and thermal gravimetric analysis. The pyrolysis tests were conducted to a final temperature of 700 °C with application of 30 minute isothermal, heating rate 10 ° C/min, N2 inert atmosphere with a flow rate of 1 L/min. The fuel gas produced in the pyrolysis process was collected at 500, 600 and 700 ° C. The tests were conducted with the reactor operating without rotation, and rotation speeds of 2 and 4 rpm. Results of chemical analysis and metals and nonmetals, show that the elephant grass has a higher concentration of lignin in relation to other perennial grasses (Switch grass/Miscanthus) as well as a high concentration of potassium (K) in its composition. The increase of the rotational speed reduced fuel gas yield fron 34.6% (0 rpm) to 19.2% (4 rpm), and increased the yield of bio-oil 37.2% (0 rpm) to 53,0% (4 rpm). The yield of biochar was not significantly influenced by the rotational speed (approximately 27% in all conditions). The presence of high amounts of potassium (K) and nitrogen (N) biochar enable its use as a source of nutrients for the soil, as well as their basic character (high pH) indicate their use to adjust the pH of acidic soils. The highest concentration of hydrogen (65% v/v) was observed in experiments without rotation of the reactor at a temperature of 700 °C. The maximum calorific value (15.128 MJ.Nm-3) was observed at a temperature of 600 °C for all investigated speed.
Nos últimos anos, a energia renovável tem recebido maior importância devido ao aumento das emissões antropogênicas de gases de efeito estufa para a atmosfera. A biomassa é um recurso renovável promissor para a produção de energia. A pirólise é uma das mais promissoras tecnologias de conversão térmica, gerando produtos de valor agregado, destacando-se de outras fontes de energias renováveis. No presente trabalho, foi abordada a conversão térmica (pirólise) do capim-elefante (Pennisetum purpureum S.) em um reator rotativo a fim de determinar as melhores condições operacionais (temperatura e rotação) para a produção de hidrogênio. O capim-elefante foi submetido a vários ensaios de caracterização, através da análise elementar (CHNS) e imediata, análise química (lignina, celulose, hemicelulose e extrativos) poder calorífico superior, análise granulométrica, análise de metais e não metais e análise termogravimétrica. Os ensaios de pirólise foram conduzidos até a temperatura final de 700 °C, com aplicação de 30 minutos de isoterma, taxa de aquecimento de 10 °C/min, atmosfera inerte com uma vazão de N2 de 1 L/min. O gás combustível produzido no processo de pirólise foi coletado a 500, 600 e 700 °C. Os ensaios foram conduzidos com o reator operando sem rotação, bem como com velocidades de rotação de 2 e 4 rpm. Resultados da análise química e de metais e não metais mostram que o capim-elefante possui maior concentração de lignina em relação a outras gramíneas perenes (Switch grass/Miscanthus), bem como uma elevada concentração de potássio (K) em sua composição. O incremento da velocidade de rotação reduziu o rendimento de gás combustível de 34,6% (0 rpm) para 19,2% (4 rpm), e aumentou o rendimento de bio-óleo 37,2% (0 rpm) para 53,0% (4 rpm). O rendimento de biochar não foi influenciado significativamente pela velocidade de rotação (aproximadamente 27% em todas as condições). A presença de elevadas quantidades de potássio (K) e nitrogênio (N) no biochar, habilitam o seu uso como fonte de nutrientes para o solo, bem como o seu caráter básico (elevado pH) indicam seu uso para ajuste de pH de solos ácidos. A maior concentração de hidrogênio (65% v/v) foi observada nos experimentos sem rotação do reator na temperatura de 700 °C. O poder calorífico máximo (15,128 MJ.Nm-3) foi observado à temperatura de 600 °C para todas as velocidades de rotação investigadas.
Keywords: Capim-elefante - Biotecnologia; Pirólise; Hidrogênio; Reatores químicos